2018
DOI: 10.1038/s41598-018-27948-3
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging reveals focal adhesions mechanoresponses in mammary epithelial cells under sustained equibiaxial stress

Abstract: Mechanical stimuli play a key role in many cell functions such as proliferation, differentiation and migration. In the mammary gland, mechanical signals such as the distension of mammary epithelial cells due to udder filling are proposed to be directly involved during lactation and involution. However, the evolution of focal adhesions -specialized multiprotein complexes that mechanically connect cells with the extracellular matrix- during the mammary gland development, as well as the influence of the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…To analyze cell anchoring points relative to surface microtopography, we sought to test zyxin expression at focal adhesion sites, consistent with its described role as an actin cytoskeleton stabilizer, sensitive to mechanical tension [ 67 ]. Its recruitment to focal adhesions is induced by cell stretching [ 68 , 69 ]. The zyxin positive focal adhesions (FAs) are distributed at the filopodia tips, where they are contacting the substrate ( Figure 5 b, Figure 6 a–d, red), thereby anchoring the actin cytoskeleton ( Figure 5 b, Figure 6 a–d, green) to the focal adhesion sites, where the filaments colocalize with zyxin ( Figure 5 b, Figure 6 a–d, yellow).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze cell anchoring points relative to surface microtopography, we sought to test zyxin expression at focal adhesion sites, consistent with its described role as an actin cytoskeleton stabilizer, sensitive to mechanical tension [ 67 ]. Its recruitment to focal adhesions is induced by cell stretching [ 68 , 69 ]. The zyxin positive focal adhesions (FAs) are distributed at the filopodia tips, where they are contacting the substrate ( Figure 5 b, Figure 6 a–d, red), thereby anchoring the actin cytoskeleton ( Figure 5 b, Figure 6 a–d, green) to the focal adhesion sites, where the filaments colocalize with zyxin ( Figure 5 b, Figure 6 a–d, yellow).…”
Section: Resultsmentioning
confidence: 99%
“…Most probably, the 33/33 µm # and 24/33 µm # isotropic patterns allowed cell-to-cell communication due to improved spreading ( Figure 5 a,b; Figure 7 a) and to less restricted directionality ( Figure 5 d). The communication through cell-cell contacts may further allow paracrine signaling activation and, consequently, retain proliferative activity [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent FRET‐based tension sensor studies , sample sizes have ranged from tens to hundreds, and statistics have been done on data that varies in length scale from subcellular structures to whole cells. Therefore, we investigated how sample size, specifically the number of cells analyzed, affects the uncertainty of FRET efficiency measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Vinculin plays an important role in sensing extracellular mechanical stimuli. For instance, conducting an equibiaxial stretching on epithelial mammary cells enhanced molecular tension across vinculin to maintain assembled focal adhesions, which revealed that vinculin could transduce external stimuli that trigger molecular reorganization in the focal adhesions (Sigaut et al, 2018 ). Furthermore, actin stress fibers are subjected to a spontaneous and random cycle of thinning and recovery, where the recruitment of paxillin and zyxin, subfamilies of LIM (Lin11, Isl-1, and Mec-3) domain proteins to stress fibers assists the recovery and stabilization of actin stress fibers at the strain sites (Smith et al, 2013 ).…”
Section: Cell-extracellular Matrix Interactionsmentioning
confidence: 99%